Factors affecting consumers’ impulse buying in live streaming commerce towards clothing and fashion products - Lau, Ka Kei (2022)
Live streaming (e.g., Facebook Live), whereby video is broadcast in real time, have been adopted by many small individual sellers as a direct selling tool. Livestreaming commerce is growing exponentially in Malaysia, while Malaysian shoppers (Generation Y and Z) are increasingly turning to the internet and benefiting from the advancement of new technology that promotes simplicity and comfort in shopping. Thus, this research is aimed to investigate the associations of influencing elements (Website Quality, Sales Promotion, Money Available, Trust, Emotion) with the impulse buying of Malaysia online shoppers on live streaming towards clothing and fashion products. Hawkins Stern Impulse Buying Theory is adopted to comprehend the relationship with impulse buying in live streaming. Throughout the study, a conceptual framework with five independent variables was created to investigate many hypotheses and the influence of variables on customers' impulsive buying in live streaming. 205 sets of questionnaires were collected from the respondents, and it is analysed by Statistical Package for the Social Sciences (SPSS) software version 26.0. Results of the research discovered that Website Quality, Sales Promotion, Money Available, and Trust are strong motivator which influence the consumers’ impulse buying in live streaming towards clothing and fashion products while Emotion is statistically insignificant on consumers’ impulse buying.